The European Union and the United States : competition, convergence and crisis in the global arena - Smith, Michael, 1947- (European Union series. Issues, 2025)
This revised edition offers a comprehensive analysis of the evolving relationship between the European Union and the United States. Framed around themes of competition, convergence, and crisis, the book explores transatlantic dynamics in trade, political economy, foreign policy, and global governance. It incorporates contemporary issues such as cybersecurity, climate change, populism, and the rise of emerging powers, providing a holistic and interdisciplinary perspective on EU–US relations. Designed for advanced undergraduate and postgraduate students, it includes case studies, summary tables, and speech extracts to support deeper understanding.